Characteristics of blood lipid and metabolic indicators in subclinical hypothyroidism patients: a retrospective study - Zhu, Lili; Jiang, Xiaohong (Frontiers in Medicine, 2024)
Background The characteristics of blood lipid and metabolic indicators were analyzed in patients with subclinical hypothyroidism (SCH), and the effect of type 2 diabetes mellitus (T2DM) on SCH patients was determined. Methods The physical examination data of 2,119 residents in a university community were retrospectively divided into 2 groups (SCH and non-SCH groups). Furthermore, the SCH group was divided into SCH-T2DM and SCH–non-T2DM subgroups, and the data between the groups were analyzed. Results The SCH group had significantly higher levels of triglycerides (p = 0.044), total cholesterol (p = 0.001), low-density lipoprotein cholesterol (p = 0.019), very low-density lipoprotein cholesterol (p = 0.044), 2-h plasma glucose (p = 0.023), and globulin (p = 0.000) compared to the non-SCH group. The SCH–T2DM group was older (p < 0.001), had a greater BMI (p = 0.028), a more rapid heart rate (p = 0.025), and a greater waist circumference (p < 0.001) than the SCH–non-T2DM group based on the subgroup analysis. The SCH–T2DM group had significantly higher dyslipidemia and dysglycemia levels than the SCH–non-T2DM group. Conclusion Patients with SCH with or without T2DM may have dyslipidemia and dysglycemia and should be evaluated accordingly.